2016
DOI: 10.1038/ncb3441
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-stimulated phosphatidylinositol-3,4,5-trisphosphate generation by scaffolded phosphoinositide kinases

Abstract: Generation of the lipid messenger phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P3) is crucial for development, cell growth and survival, and motility, and it becomes dysfunctional in many diseases including cancers. Here we reveal a mechanism for PtdIns(3,4,5)P3 generation by scaffolded phosphoinositide kinases. In this pathway, class I phosphatidylinositol-3-OH kinase (PI(3)K) is assembled by IQGAP1 with PI(4)KIIIα and PIPKIα, which sequentially generate PtdIns(3,4,5)P3 from phosphatidylinositol. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(196 citation statements)
references
References 79 publications
(110 reference statements)
9
173
0
Order By: Relevance
“…The cells were grown at 37 C until an OD600 of 1.0 was reached, at which point they were induced by 0.3 mmol/L isopropyl b-D-thiogalactoside at 16 C for 18 hours. The cells were then harvested and resuspended in buffer containing 50 mmol/L HEPES (pH 7.5), 1 mol/L NaCl, 2 mmol/L DTT, 20 mmol/L MgCl 2 , 1 mmol/L phenylmethylsulfonyl fluoride, and 1 mg/mL lysozyme.…”
Section: Virtual Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were grown at 37 C until an OD600 of 1.0 was reached, at which point they were induced by 0.3 mmol/L isopropyl b-D-thiogalactoside at 16 C for 18 hours. The cells were then harvested and resuspended in buffer containing 50 mmol/L HEPES (pH 7.5), 1 mol/L NaCl, 2 mmol/L DTT, 20 mmol/L MgCl 2 , 1 mmol/L phenylmethylsulfonyl fluoride, and 1 mg/mL lysozyme.…”
Section: Virtual Screeningmentioning
confidence: 99%
“…For measurement of PI4P in tumor tissues, lipids extracted from equal weights (approximately 10 mg) of xenograft tumors were analyzed for PI4P using the PI4P Mass ELISA Kit described above and normalized by the tissue weights. Statistical analysis was performed with 6 paired cases (37).…”
Section: Thermal Shift Assay and Cellular Thermal Shift Assaymentioning
confidence: 99%
“…For example, in the Ras-ERK pathway, Raf, MEK, and ERK interact with IQGAP1, which physically links the kinases in close proximity to facilitate their sequential phosphorylation (Ren et al, 2007). Recently, a scaffold role for IQGAP1 in the PI3K-Akt pathway has been revealed (Choi et al, 2016). In response to receptor activation, PI4KIIIa, PIPKIa, and PI3K are assembled by IQGAP1 and this results in sequential generation of phosphatidylinositol-3,4,5-trisphosphate (PI3,4,5P 3 ) from phosphatidylinositol.…”
mentioning
confidence: 99%
“…Moreover the insulin-induced phosphorylation of PKB was reduced in liver and muscle tissue of IQGAP1 knock out animals compared to wt [116]. In different cell lines, IQGAP1 was shown to interact with IR via its IQ domains, and the PTB domain of IRS1 to interact with the RGCT domain of IQGAP1 [117].…”
Section: Figure 6 Fluorescence Microscopic Images Demonstrating the mentioning
confidence: 93%
“…Using various cancer cell-lines it was shown that upon agonist stimulation IQGAP1 binds all the phosphoinositide kinases needed for sequential phosphorylation of phosphatidylinositol to PIP3, including PI3K, as well as the downstream substrates of PI3K: PKB and PDK1 [116].…”
Section: Figure 6 Fluorescence Microscopic Images Demonstrating the mentioning
confidence: 99%